In search of Africa - Diawara, Manthia; Diawara, Manthia, 1953-; Newsreel (Firm) ([New York : harvad university press, 1998)
"In 1996, the filmmaker and writer Manthia Diawara, now living in New York, returns to Guinea, thirty-two years after he and his family were expelled from the newly liberated country. Despite the years that have gone by, Diawara expects to be welcomed as an insider, and is shocked to discover that he is not."-- Distributor Website.
Originally produced in 1996.
Disc label incorrectly lists running time as 26 min.
Camera, Manthia Diawra and others ; editors, Beverly Petterrson, Lora Hayes.
DVD; stereo.
In English and French with English subtitles.
Keywords: Diawara, Manthia, -- 1953- -- Travel -- Guinea; West Africans -- United States -- Ethnic identity; African Americans -- Relations with Africans; Pan-Africanism.; United States -- Relations -- Africa, French-speaking West; Africa, French-speaking West -- Relations -- United States